Neuraxial anesthesia versus general anesthesia for urological surgery: systematic review - Barbosa, Fabiano Timbó (2013)
CONTEXT AND OBJECTIVE: Choosing the best anesthetic technique for urological surgery with the aim of mortality reduction remains controversial. The objective here was to compare the effectiveness and safety of neuraxial anesthesia versus general anesthesia for urological surgery. DESIGN AND SETTING: Systematic review, Universidade Federal de Alagoas. METHODS: We searched the Cochrane Central Register of Controlled Trials in the Cochrane Library (Issue 10, 2012), Medline via PubMed (1966 to October 2012), Lilacs (1982 to October 2012), SciELO and EMBASE (1974 to October 2012). The reference lists of the studies included and of one systematic review in the same field were also analyzed. The studies included were randomized controlled trials (RCT) that analyzed neuraxial anesthesia and general anesthesia for urological surgery. RESULTS: The titles and abstracts of 2720 articles were analyzed. Among these, 16 studies were identified and 11 fulfilled the inclusion criteria. One RCT was published twice. The study validity was: Jadad score > 3 in one RCT; seven RCTs with unclear risk of bias as the most common response; and five RCTs not fulfilling half of the Delphi list items. The frequency of mortality was not significant between study groups in three RCTs. Meta-analysis was not performed. CONCLUSION: At the moment, the evidence available cannot prove that neuraxial anesthesia is more effective and safer than general anesthesia for urological surgery. There were insufficient data to pool the results relating to mortality, stroke, myocardial infarction, length of hospitalization, quality of life, degree of satisfaction, postoperative cognitive dysfunction and blood transfusion requirements.